PENGEMBANGAN HOLE BALL SEBAGAI PERMAINAN BOLA KECIL DALAM PEMBELAJARANPENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN BAGI SISWA SD KELAS V - SLAMET SANTOSO (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2015)
Hole Ball Development As A Smallball Game in Learning Physical Education, Sports, and Health at Fifth Grade of Elementary Schools. Hole Ball game is one of the alternative of games of sport that could be taught to the students so that they did not feel bored when they studied smallball game and It had a purpose to increase the students ability of throwing and catching. The results of this study are (1) Hole ball game model as a smallball game. (2) the effectiveness of the games model could improve students throwing and catching ability. It could be seen from the improvement before and after following the learning of Hole ball game. The average improvment of students throwing and catching ability after learning process has increased by 21.82%. (3) this hole ball game model could overcome the limitations of the existing of structure and infrastructure. The conclusions of this study are 1) Hole ball game can be used in the learning of smallball. 2) Hole ball learning can increase throwing and catching ability effectivelly. 3) this game as smallball game is accepted in Physical education, sports, and health learning.